Pengaruh Model Diskusi Kelompok Kecil (Small Group Discussion) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PPKN Di SMAS Santo Thomas 2 Medan - Kaunang, Piteryan; Pasaribu, Kondios Meidarlin; Siahaan, Monalisa Marta (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This research is motivated by the fact that the learning process in Civic Education (PPKn) still tends to be teacher-centered (conventional), causing students to be less active and face difficulties in understanding concepts deeply. The purpose of this research is to determine and analyze the extent of the influence of implementing the Small Group Discussion (SGD) learning model on students’ cognitive learning outcomes in PPKn subjects at SMAS Santo Thomas 2 Medan. The research method used is a quantitative approach with a quasi-experimental design. The research population included all grade X students of SMAS Santo Thomas 2 Medan, totaling 406 students. The research sample consisted of two classes selected through a quasi-sampling technique: class X MB 8 as the experimental group (33 students) and class X MB 3 as the control group (34 students). Data were collected through pretest and posttest instruments that had been tested for validity and reliability. Data analysis techniques included normality tests, homogeneity tests, Independent Sample T-Tests, and N-Gain analysis using the SPSS program. The results showed a significant influence of the SGD model implementation on student learning outcomes. This is evidenced by the increase in the average score of the experimental class from 62.45 in the pretest to 81.27 in the posttest. The t-test results showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, meaning the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Furthermore, the N-Gain analysis yielded a value of 0.6528, which falls into the "medium" category, indicating that the SGD model is quite effective in improving student understanding. The conclusion of this study is that the application of the Small Group Discussion learning model provides a positive and significant impact on improving students’ PPKn learning outcomes.